A new approach to spectral line shapes of the weak oxygen transitions for atmospheric applications. (January 2016) - Domysławska, Jolanta; Wójtewicz, Szymon; Masłowski, Piotr; Cygan, Agata; Bielska, Katarzyna; Trawiński, Ryszard S.; Ciuryło, Roman; Lisak, Daniel
Abstract: We propose to construct a new database of O2 molecular spectral lines for atmospheric application, consistent with recent IUPAC recommendation [Tennyson et al. Pure Appl Chem 2014;86:1931] going beyond Voigt profile by incorporation of the speed dependence of collisional broadening and shifting. For this purpose we collected the laboratory data for the self-perturbed oxygen B-band transitions. Line shapes were measured at low pressures by the Pound–Drever–Hall-locked frequency-stabilized cavity ring-down spectrometer linked to the optical frequency comb. Data were analyzed by means of the quadratic speed-dependent Voigt profile. The absolute transition frequencies are determined with accuracy even as good as 150 kHz. Line intensities, pressure width and shift coefficients and the speed-dependent parameters are determined with subpercent accuracy.